Activity of aztreonam-avibactam and ceftazidime-avibactam against β-lactamase-producing enterobacterales Isolates from United States hospitals - Lalitagauri M Deshpande; Timothy B Doyle; Helio S Sader; Mariana Castanheira (Journal of Global Antimicrobial Resistance, 2025)
Objectives: Enterobacterales isolates producing β-lactamases are widespread and threaten the use of β-lactams. This study evaluated the activity of aztreonam-avibactam and comparator antimicrobial agents against Enterobacterales isolates producing common β-lactamases collected in US hospitals. Methods: A total of 18,148 Enterobacterales isolates collected during 2020–2021 in US hospitals (n = 71) were susceptibility tested by reference broth microdilution methods. A total of 2,337 isolates were submitted to whole genome sequencing due to elevated cephalosporins/aztreonam MIC values or carbapenem nonsusceptibility (meropenem and/or imipenem MIC results at >1 mg/L). Results: ESBL enzymes were observed among 1,430 carbapenem-susceptible E. coli, K. pneumoniae, E. cloacae and Citrobacter spp. isolates and CTX-M-15 was the most common ESBL. Ceftazidime-avibactam inhibited all ESBL-producers while ceftolozane-tazobactam inhibited 68.4–95.9%. Aztreonam-avibactam inhibited >99.7% of the isolates regardless of the ESBL type or organism. Among other classes, amikacin and tigecycline were the most active agents, inhibiting 78.5% and 97.8% of the ESBL-producing isolates. All isolates carrying transferrable AmpC genes were susceptible to ceftazidime-avibactam and meropenem-vaborbactam, and 98.1% susceptible to aztreonam-avibactam, but only 83.3% were susceptible to ceftolozane-tazobactam. Five isolates carried blaCMY-42 with a PBP3 insertion and they exhibited aztreonam-avibactam MICs ranging from 2 to 16 mg/L. Among carbapenemase-producers (n = 157), aztreonam-avibactam, ceftazidime-avibactam and meropenem-vaborbactam susceptibility rates were 98.7%, 81.5% and 79.6%. The only comparator displaying activity against these isolates was tigecycline (93.0% susceptible). Conclusions: New β-lactam/β-lactamase inhibitors were active against common β-lactamase-producing isolates from US hospitals, including carbapenemase-producing isolates for which therapeutic options are limited. Aztreonam-avibactam was the most active agent against carbapenemase producers, including MBL-carrying isolates.